Legal Analysis Towards Mining in North Sulawesi Post the Implementation of Law Number 3 Year 2020 - Hasyim Sofyan Lahilote (IAIN Manado, 2021)
The issuance of Law No. 3 of 2020 as an amendment to Law No. 4 of 2009 concerning Mineral and Coal Mining, has changed the supervisory mechanism for the implementation of mineral and coal mining in the regions. This study aimed at analyzing the legal mining exploration in the regions associated with the principle of decentralization based on regional autonomy. The method used in this study is empirical juridical, and the results obtained illustrate that the issuance of the new mineral and coal law will cause a minimum role for local governments, both provincial, district and/or city in monitoring mining in the regions, especially in terms of mining exploration. It is because the monitoring system for mining exploration becomes centralized and effects on reducing regional revenue potential.